EFEKTIVITAS PROMOSI KESEHATAN TERHADAP PERUBAHAN PENGETAHUAN TENTANG PERILAKU HIDUP BERSIH DAN SEHAT PADA TATANAN RUMAH TANGGA DI KELURAHAN PEBATUAN (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2025)
PHBS represents the creation of a conducive condition for the community to improve knowledge, attitudes, and health behaviors. The impact of unhealthy behaviors and environments in the community will lead to various infectious diseases. The purpose of the research is to determine the effectiveness of health promotion on changes in knowledge about PHBS in the household setting in the Pebatuan Village. This is a quantitative research type with a pre-experimental design using a one-group pretest-posttest approach. The population for this study consists of 94 individuals. The sample for this study was selected through purposive sampling using the Lemeshow formula, resulting in a total of 38 individuals. Data was obtained through the distribution of questionnaires. Data analysis was performed using a non-parametric test, specifically the Wilcoxon rank test. The results of the study showed that the percentage of respondents with insufficient knowledge of exclusive breastfeeding before health promotion was 55.3%, and the percentage with good knowledge of exclusive breastfeeding after health promotion was 84.2%. The percentage of respondents with insufficient knowledge of weighing infants/children before health promotion was 78.9%, while the percentage with good knowledge of weighing infants/children after health promotion was 73.7%. The study results indicated that health promotion is effective in increasing knowledge about PHBS (Clean and Healthy Living Behavior) with a p-value of 0.000
Keywords: PHBS Household; Health Promotion